SAT0037 Duration of Immune Response To Influenza Vaccination in Patients with Rheumatoid Arthritis Treated with Biological Agents. (15th July 2016) - Yuklyaeva, N.; Lawrence, D.A.; Raddatz, D.; Kasten-Jolly, J.; Scribani, M.; Victory, J.; Tirrell, J.; Chaudhary, A.A.; Sornprom, S.; Sanguankeo, A.
Abstract : Background: After influenza vaccination, limited data is available to prove effective anti-influenza status at the end of the season 1 . Objectives: To assess the strength and duration of response to trivalent influenza vaccine (A-California/07/2009(H1N1), A/Texas/50/2012 (H3N2), B/Massachusetts/02/2012) in patients with rheumatoid arthritis (RA) receiving biological agents. Methods: Sera were collected prior to vaccination, and 4–6 weeks and 5–6 months thereafter. The vaccine was given in the age-appropriate dose recommended by the manufacturer. Antibody response to vaccination was measured by detection of vaccine-specific IgG using ELISA. Hemagglutination inhibition assay (HIA) was used to determine patients who were seroprotected (titer>1:40) prior to vaccination, and patients seroconverted (≥4-fold increase) post-vaccination 2 . Results: Study comprised of 88 subjects, 16 in Anti-T cell agent (abatacept) group, 35 in anti-TNF (adalimumab, certolizumab, etanercept, golimumab, infliximab) group and 37 were age-matched healthy controls. When tested by HIA, all subjects fulfilled the criteria for seroprotection prior to vaccination and only one patient failed to seroconvert by the end of the season. Levels of vaccine-specific IgG (mean±SE) for each of the groups with respect to each time point were: control group pre-vaccination 111.07±11.05 μg, 6 weeks post-vaccination 149.19±11.76 μg and 6 months post-vaccination 114.62±8.94 μg; Anti-T-cell group pre-vaccination 140.93±15.41 μg, 6 weeks post vaccination 151.33±16.4 μg and 6 months post vaccination 112.22±12.47 μg; Anti-TNF group pre-vaccination 134.33±10.63 μg, 6-weeks post vaccination 170.96±11.31 μg and 6-months post vaccination 130.67±8.6 μg. The three-way ANOVA model produced a statistically significant two-way interaction of diagnostic group*time (p=.0446) indicating a differential pattern of antibody response across the groups, with a more moderate slope between pre-vaccination and 6 weeks post-vaccination among the Anti-Tcell group as compared to the other two groups. Statistically significant positive correlations were found between baseline titer and titer at 6 weeks and 6 months post-vaccination for each of the three diagnostic groups tested individually. There was no correlation between RA and treatment duration with antibody titers at 6 weeks and 6 months post-vaccination. Conclusions: The study suggests that anti-Tcell therapy may affect the strength and duration of IgG-mediated immune response and protection may fade away before the end of the influenza season. At the same time, response of patients on anti-TNF therapy was comparable to the control group. HIA results indicated all patients were seroprotected at the baseline and nearly all seroconverted whereas ELISA analysis helped reveal the more subtle dynamics of the immune response. References: Adler S, Krivine A, Weix J, Rozenberg F, Launay O, Huesler J, Guillevin L, Villiger PM. Protective effect of A/H1N1 vaccination in immune-mediated disease-a prospectively controlled vaccination study. Rheumatology (Oxford). 2012 Apr; 51(4):695–700. Prevention and Control of Seasonal Influenza with Vaccines: Recommendations of the Advisory Committee on Immunization Practices – United States, 2013–2014. Disclosure of Interest: None declared